Graphene Oxide as a Nanocarrier for Controlled Loading and Targeted Delivery of Typhonium giganteum Drugs - Xiaohua Gu; Rui Cao; Fu Li; Yan Li; Hongge Jia; Hui Yu (Journal of Chemistry)
In this study, Typhonium giganteum containing dual-function nanofibers composed of poly(butylene carbonate), polylactic acid, and graphene oxide (PBC/PLA/GO) were successfully fabricated by electrospinning. The results from thermogravimetric analysis (TG), differential scanning calorimetry (DSC), and Fourier-transform infrared spectroscopy (FTIR) indicate that no interactions occurred between PBC and PLA. The nanofiber microstructure upon which graphene oxide was evenly distributed was studied by scanning electron microscopy (SEM) and showed good silk properties. The nanofibers can be used as a drug carrier since loaded Typhonium giganteum fibers possess excellent biocompatibility. Such nanofibers are effective in inhibiting the proliferation of A549 lung cancer cells, and thus they have potential for replacing chemotherapy-based treatments of lung cancer. In addition, the PBC/PLA/GO nanofibers degrade in physiological and natural environments, which is an important feature when engineering tissues and environment-friendly materials.